Q: What is the base in 9b to the second power?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4

9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)

The simplified expression is -9a -9b.

(12a+9b)(12a-9b)

You would factor 3a + 9b as: 3(a+3b)

Related questions

(27a)2 = 729a2 (9b)3 = 729b3 So (27a)2 + (9b)3 = 729*(a2 + b3)

9b2b is the base.==========9 is the coefficient of the variable term.2 is the exponent.

The common term for raising a base to the second power is to square it.Base^2

6 is the base number.

Since 3b is a factor of 9b, it is automatically the GCF.

3A + 9B = 3(A + 3B)

9

2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4

9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)

The simplified expression is -9a -9b.

(12a+9b)(12a-9b)

the length of the base would be 16